Nε-Carboxymethyl-Lysine Negatively Regulates Foam Cell Migration via the Vav1/Rac1 Pathway - Zhengyang Bao; Lili Zhang; Lihua Li; Jinchuan Yan; Qiwen Pang; Zhen Sun; Yue Geng; Lele Jing; Chen Shao; Zhongqun Wang (Journal of Immunology Research)
Background. Macrophage-derived foam cells play a central role in atherosclerosis, and their ultimate fate includes apoptosis, promotion of vascular inflammation, or migration to other tissues. Nε-Carboxymethyl-lysine (CML), the key active component of advanced glycation end products, induced foam cell formation and apoptosis. Previous studies have shown that the Vav1/Rac1 pathway affects the macrophage cytoskeleton and cell migration, but its role in the pathogenesis of diabetic atherosclerosis is unknown. Methods and Results. In this study, we used anterior tibiofibular vascular samples from diabetic foot amputation patients and accident amputation patients, and histological and cytological tests were performed using a diabetic ApoE-/- mouse model and primary peritoneal macrophages, respectively. The results showed that the atherosclerotic plaques of diabetic foot amputation patients and diabetic ApoE-/- mice were larger than those of the control group. Inhibition of the Vav1/Rac1 pathway reduced vascular plaques and promoted the migration of macrophages to lymph nodes. Transwell and wound healing assays showed that the migratory ability of macrophage-derived foam cells was inhibited by CML. Cytoskeletal staining showed that advanced glycation end products inhibited the formation of lamellipodia in foam cells, and inhibition of the Vav1/Rac1 pathway restored the formation of lamellipodia. Conclusion. CML inhibits the migration of foam cells from blood vessels via the Vav1/Rac1 pathway, and this process affects the formation of lamellipodia.